2019
DOI: 10.1248/cpb.c18-01018
|View full text |Cite
|
Sign up to set email alerts
|

Novel Dissolution Approach for Tacrolimus-Loaded Microspheres Using a Dialysis Membrane for <i>in Vitro</i>–<i>in Vivo</i> Correlation

Abstract: The aim of this study was to establish a novel approach to in vitro dissolution evaluation using a combination of the paddle method and a dialysis membrane, both to predict the overall in vivo performance of tacrolimus microspheres and also to identify a suitable dissolution test method to describe the in vivo initial burst phenomenon. This new dissolution method for evaluating the release of tacrolimus from microspheres consisted of rotating a customized paddle inside a dialysis membrane using a conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Recently, Park et al reported good IVIVC of PLGA microparticles containing norquetiapine ( N -desalkyl quetiapine), which is an active metabolite of quetiapine, where point-to-point relationship of r 2 greater than 0.98 between in vitro release (SS method) and in vivo release in rats was obtained [ 110 ]. Recently, Kaihara et al developed an in vitro release testing method by rotating a customized paddle inside a dialysis membrane to predict the in vivo drug release properties of tacrolimus-loaded microparticles [ 111 ]. This study found that it may not be possible to predict both the overall drug release profile and the initial burst using a single method.…”
Section: In Vitro–in Vivo Correlation (Ivivc)mentioning
confidence: 99%
“…Recently, Park et al reported good IVIVC of PLGA microparticles containing norquetiapine ( N -desalkyl quetiapine), which is an active metabolite of quetiapine, where point-to-point relationship of r 2 greater than 0.98 between in vitro release (SS method) and in vivo release in rats was obtained [ 110 ]. Recently, Kaihara et al developed an in vitro release testing method by rotating a customized paddle inside a dialysis membrane to predict the in vivo drug release properties of tacrolimus-loaded microparticles [ 111 ]. This study found that it may not be possible to predict both the overall drug release profile and the initial burst using a single method.…”
Section: In Vitro–in Vivo Correlation (Ivivc)mentioning
confidence: 99%